Regulation of Sexual Commitment and Gametocytogenesis in Malaria Parasites - Gabrielle A. Josling; Kim C. Williamson; Manuel Llinás (2018)
Sexual differentiation of malaria parasites from the asexual blood stage into gametocytes is an essential part of the life cycle, as gametocytes are the form that is taken up by the mosquito host. Because of the essentiality of this process for transmission to the mosquito, gametocytogenesis is an extremely attractive target for therapeutic interventions. The subject of this review is the considerable progress that has been made in recent years in elucidating the molecular mechanisms governing this important differentiation process. In particular, a number of critical transcription factors and epigenetic regulators have emerged as crucial elements in the regulation of commitment. The identification of these factors has allowed us to understand better than ever before the events occurring prior to and during commitment to sexual development and offers potential for new therapeutic interventions.